2012
DOI: 10.1371/journal.pone.0050138
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine Protects Neuronal Cell Death and Induces Heme Oxygenase-1 Expression in Mes23.5 Dopaminergic Neurons

Abstract: BackgroundDesipramine is known principally as a tricyclic antidepressant drug used to promote recovery of depressed patients. It has also been used in a number of other psychiatric and medical conditions. The present study is the first to investigate the neuroprotective effect of desipramine.Methodology/Principal FindingsMes23.5 dopaminergic cells were used to examine neuroprotective effect of desipramine. Western blot, reverse transcription-PCR, MTT assay, siRNA transfection and electrophoretic mobility shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 83 publications
1
30
0
Order By: Relevance
“…It has been identified as a potential therapeutic target in CNS inflammatory and neurodegenerative diseases. Our previous study also revealed that CoPP protected neuronal cells against rotenone-and 6-hydroxydopamine-induced neuronal death [20]. CoPPinduced HO-1 may offer a protective role in cold injuryinduced cerebral cortex damage and neurological/behavioral impairment [64].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been identified as a potential therapeutic target in CNS inflammatory and neurodegenerative diseases. Our previous study also revealed that CoPP protected neuronal cells against rotenone-and 6-hydroxydopamine-induced neuronal death [20]. CoPPinduced HO-1 may offer a protective role in cold injuryinduced cerebral cortex damage and neurological/behavioral impairment [64].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, induction of HO-1 expression also contributes to the anti-inflammatory effects in murine macrophages through suppressing iNOS and COX-2 expression [18]. We have published several studies that induction of HO-1 expression is a potential therapeutic strategy for microglial-related neuroinflammatory responses [19] and neuroprotective effects [20][21]. The significant facts indicated that the importance of HO-1 in regulation inflammatory response HO-1 reduces microglia activation by inhibiting ROS production and via PI3K/Akt signaling pathways [22].…”
Section: Introductionmentioning
confidence: 99%
“…NQO1 is a cytoplasmic two electron reductase that catalyzes the reduction of a wide range of substrates, including quinones, quinone-imines, and nitro-compounds [31] . Thus, the up-regulation of HO-1 and NQO1 in response to oxidative stresses provides an effective endogenous antioxidant defense mechanism in rotenone-induced PC12 cells [32,33] . To determine whether the Nrf2/ARE/HO-1 signaling pathway is involved in the neuroprotective effect of 20C, we investigated the changes in the Nrf2/ARE/HO-1 signaling pathway in the 20C-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates a dual role of Ccl2 in neuronal survival [86,87]. While drugs like bindarit downregulate Ccl2 and protect neurons [88], noradrenaline transporter inhibitors like desipramine elicit neuroprotection by upregulating the expression of Ccl2 [89,90].…”
Section: Chemokine Mapk and Tnf Signalingmentioning
confidence: 99%